HUBUNGAN PERAWATAN TALI PUSAT DENGAN KEJADIAN INFEKSI PADA BAYI BARU LAHIR DI RSUD Dr. PIRNGADI MEDAN 2019 - Damanik, Rani (Jurnal Keperawatan Priority, 2019)
Umbilical cord care is one treatment procedure that aims to treat the umbilical cord in newborns to keep it dry and prevent infection. Improper treatment of the umbilical cord in an infant will experience an infectious disease. This study uses a correlation design with a cross sectional approach is something that connects / analyzes the variables that aim to determine the relationship of umbilical cord care with the incidence of infection in newborns (BBL) in RSUD Dr. Pirngadi Hospital Medan 2018, with a sample of 35 respondents. The instruments included demographic data, 20 umbilical cord care questionnaires and observation sheets for infection. Based on the results of this study, the majority of people doing good umbilical cord care (score 14-20) as many as 30 (85.7%) while the minority of respondents doing umbilical cord care enough (score 7-13) as many as 5 people (14.2%). the majority did not experience an infection score of 0 (zero) as many as 33 people (94.3%) and the minority experienced infection score 1-5 as many as 2 people (5.7%). Based on Chi Square test, p = 0.017 <0.05 means that Ho is rejected and Ha is accepted. This shows a relationship between cord care and the incidence of infection in newborns (BBL). It is expected that nurses to carry out umbilical cord care measures more effectively in accordance with the SOP so as to avoid the number of infections in newborns and the next researcher makes an observation sheet in measuring cord care performed by nurses.